Contribution of Ash Content Related to Methane Adsorption Behaviors of Bituminous Coals - Yanyan Feng; Wen Yang; Wei Chu (International Journal of Chemical Engineering)
Methane adsorption isotherms on coals with varying ash contents were investigated. The textural properties were characterized by N2 adsorption/desorption isotherm at 77 K, and methane adsorption characteristics were measured at pressures up to 4.0 MPa at 298 K, 313 K, and 328 K, respectively. The Dubinin-Astakhov model and the Polanyi potential theory were employed to fit the experimental data. As a result, ash content correlated strongly to methane adsorption capacity. Over the ash range studied, 9.35% to 21.24%, the average increase in methane adsorption capacity was 0.021 mmol/g for each 1.0% rise in ash content. With the increasing ash content range of 21.24%~43.47%, a reduction in the maximum adsorption capacities of coals was observed. In addition, there was a positive correlation between the saturated adsorption capacity and the specific surface area and micropore volume of samples. Further, this study presented the heat of adsorption, the isosteric heat of adsorption, and the adsorbed phase specific heat capacity for methane adsorption on various coals. Employing the proposed thermodynamic approaches, the thermodynamic maps of the adsorption processes of coalbed methane were conducive to the understanding of the coal and gas simultaneous extraction.